The relationship between the level of knowledge about cross-infection control and its compliance among students at jenderal achmad yani university dental hospital: Cross sectional study - Kamila, Syadza Afifah; Mulyanti, Sri; Utami, Ulfah; Nurnaningsih, Hera (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Due to their frequent contact with blood and saliva while providing dental care, dental healthcare personnel are particularly vulnerable to infection transmission. According to a preliminary study, a large number of students have not yet put cross-infection control procedures into place, even though doing so may raise their risk of coming into contact with pathogens. The purpose of this research is to ascertain how students at the RSGM UNJANI relate to their level of cross-infection control knowledge and their compliance with its implementation. Methods: This type of research is analytical research with a cross-sectional research design with a sample of 60 students at UNJANI RSGM. Data collection using questionnaires and observation. Results: The results of the survey indicate that the students' knowledge levels fall into three categories: